2015
DOI: 10.1186/s12890-015-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of exacerbations in patients with COPD and vitamin D deficiency through vitamin D supplementation (PRECOVID): a study protocol

Abstract: BackgroundVitamin D is well known for its function in calcium homeostasis and bone mineralisation, but is increasingly studied for its potential immunomodulatory properties. Vitamin D deficiency is a common problem in patients with COPD. Previous studies have not demonstrated a beneficial effect of vitamin D on exacerbation rate in COPD patients. However, subgroup analyses suggested protective effects in vitamin D deficient patients. Our objective is to assess the effect of vitamin D supplementation on exacerb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 66 publications
(81 reference statements)
2
22
0
Order By: Relevance
“…In this study, Rafiq et al 62 will also reported a significant reduction in the levels of tumor necrosis factor α at week 12.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…In this study, Rafiq et al 62 will also reported a significant reduction in the levels of tumor necrosis factor α at week 12.…”
supporting
confidence: 61%
“…The study of Rafiq et al 62 and a subsequent meta--analysis will finally address the issue of whether vitamin D supplementation in deficient patients with COPD should be recommended in a clinical setting to reduce exacerbations and improve physical functioning. increased in the supplemented group compared with placebo, particularly in the group with severe vitamin D deficiency.…”
mentioning
confidence: 99%
“…Since the study was small and it reported a protective effect of vitamin D supplementation against exacerbations, the effect of its omission, if any, may have been to slightly bias results of this meta-analysis towards the null. We are aware of at least one ongoing RCT of vitamin D supplementation for the prevention of COPD exacerbations25 (n=240, scheduled to complete follow-up in 2019). Inclusion of IPD from this study and other eligible studies in a future meta-analysis has potential to increase power for subgroup analyses and generalisability of results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study by Lehouck et al65 held inconsistent results that vitamin D supplementation had no effect on the rate of COPD exacerbations. A study exploring the effect of vitamin D supplementation on the incidence of exacerbations in vitamin D deficiency comorbid COPD patients is in progress 66. Maybe, it can broaden our knowledge of vitamin D and COPD exacerbation.…”
Section: Discussionmentioning
confidence: 99%